3D phase‐resolved functional lung ventilation MR imaging in healthy volunteers and patients with chronic pulmonary disease. Issue 2 (14th September 2020) - Klimeš, Filip; Voskrebenzev, Andreas; Gutberlet, Marcel; Kern, Agilo Luitger; Behrendt, Lea; Grimm, Robert; Suhling, Hendrik; Crisosto, Cristian Gonzales; Kaireit, Till Frederick; Pöhler, Gesa Helen; Glandorf, Julian; Wacker, Frank; et al.
Abstract : Purpose: To test the feasibility of 3D phase‐resolved functional lung (PREFUL) MRI in healthy volunteers and patients with chronic pulmonary disease, to compare 3D to 2D PREFUL, and to investigate the required temporal resolution to obtain stable 3D PREFUL measurement. Methods: Sixteen participants underwent MRI using 2D and 3D PREFUL. Retrospectively, the spatial resolution of 3D PREFUL (4 × 4 × 4 mm 3 ) was decreased to match the spatial resolution of 2D PREFUL (4 × 4 × 15 mm 3 ), abbreviated as 3Dlowres . In addition to regional ventilation (RVent), flow‐volume loops were computed and rated by a cross‐correlation (CC). Ventilation defect percentage (VDP) maps were obtained. RVent, CC, VDPRVent, and VDPCC were compared for systematic differences between 2D, 3Dlowres, and 3D PREFUL. Dividing the 3D PREFUL data into 4‐ (≈ 20 phases), 8‐ (≈ 40 phases), and 12‐min (≈ 60 phases) acquisition pieces, the ventilation parameter maps, including the heterogeneity of ventilation time to peak, were tested regarding the required temporal resolution. Results: RVent, CC, VDPRVent, and VDPCC presented significant correlations between 2D and 3D PREFUL ( r = 0.64‐0.94). CC and VDPCC of 2D and 3Dlowres PREFUL were significantly different ( P < .0113). Comparing 3Dlowres and 3D PREFUL, all parameters were found to be statistically different ( P < .0045). Conclusion: 3D PREFUL MRI depicts the whole lung volume and breathing cycle with superior image resolution and with likely more precision compared to 2D PREFUL. Furthermore, 3D PREFUL is more sensitive to detect regions of hypoventilation and ventilation heterogeneity compared to 3Dlowres PREFUL, which is important for early detection and improved monitoring of patients with chronic lung disease.